Translation Orientation of Culture-Specific Items in Novel Ronggeng Dukuh Paruk from Indonesian to German - Cynthia Yanda Salsabila; Sajarwa Sajarwa (Jurnal Pendidikan Bahasa dan Sastra, 2022)
One of the salient problems in translation arises when it comes to translation of cultural words or terms as each language may have its own set of terms. Therefore, this research deals with the orientation in translating culture-specific items from the source language to the target language. The research approach employed in this paper is descriptive qualitative. The data on culture-specific items are obtained based on Newmark’s (1988) categories and translation procedures. The obtained results indicate that the most frequently found CSI category in the data is material culture. Then, the prevailing translation procedures used to render cultural words in Ronggeng Dukuh Paruk’s novel were transference, functional equivalent, descriptive equivalent, recognized translation, componential analysis, reduction, couplets, notes and glosses. From the translation procedures conducted by translator, the orientation can be implied. The theory of translation orientation proposed by Venuti (1995) was followed. The analysis has revealed that the functional equivalent descriptive equivalent, cultural equivalent, component analysis, recognized translation, reduction, and glossary procedures are the most commonly used procedures. Thus, it implies that the translation of Indonesian CSIs in RDP into the target text orientates toward TL or domestication.